2013
DOI: 10.1021/jm4006274
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Kinesin Eg5 Overcomes Inhibition to the Phase I/II Clinical Candidate SB743921 by an Allosteric Resistance Mechanism

Abstract: Development of drug resistance during cancer chemotherapy is one of the major causes of chemotherapeutic failure for the majority of clinical agents. The aim of this study was to investigate the underlying molecular mechanism of resistance developed by the mitotic kinesin Eg5 against the potent second-generation ispinesib analogue SB743921 (1), a phase I/II clinical candidate. Biochemical and biophysical data demonstrate that point mutations in the inhibitor-binding pocket decrease the efficacy of 1 by several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…In this connection, it was reported that Ispinesib‐resistant HCT116 cells contain two point mutations in the KIF11 allosteric binding pocket, D130V and A133D, generating inhibitor‐resistant but otherwise catalytically competent KIF11 (Knight and Parrish, 2008). Interestingly, the mutations do not act through conventional steric effects at the binding site, but through reduction of flexibility and allosteric transmissions after inhibitor binding (Talapatra et al., 2013). Finally, another process specific for antimitotic drug‐resistance is mitotic slippage, by which cells exit mitosis prematurely without sister chromatid separation.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, it was reported that Ispinesib‐resistant HCT116 cells contain two point mutations in the KIF11 allosteric binding pocket, D130V and A133D, generating inhibitor‐resistant but otherwise catalytically competent KIF11 (Knight and Parrish, 2008). Interestingly, the mutations do not act through conventional steric effects at the binding site, but through reduction of flexibility and allosteric transmissions after inhibitor binding (Talapatra et al., 2013). Finally, another process specific for antimitotic drug‐resistance is mitotic slippage, by which cells exit mitosis prematurely without sister chromatid separation.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the exception of ARRY-520, the clinical experience with Eg5 and CENP-E inhibitors in phase I trials has been disappointing, and in the case of ispinesib and AZD-4877, this lack of effi cacy has been confi rmed by subsequent phase II trials. There are several explanations for these results: First, an obvious explanation is the development of tumor resistance, due to point mutations within L5-a loop in the Eg5 enzymatic domain that constitutes part of the drug-binding site [ 58 ]. The genetic instability that is characteristic of most malignant tumors might allow for selection of Eg5 mutations that confer treatmentresistance.…”
Section: Summary Of the Clinical Experience With Mitotic Kinesin Inhimentioning
confidence: 99%
“…D130, A133) and deletions (e.g. residues in ‘loop-5’) within this pocket have been shown to confer resistance to ispinesib-analogs in vitro 19 . Therefore, with these data, we can confirm kinesin-5 to be ispinesib’s direct physiologic target in a human cancer cell line.…”
mentioning
confidence: 99%